Produção de farinha instantânea de mandioca: efeito das condições de extrusão sobre as propriedades térmicas e de pasta - Borges Lustosa, Beatriz Helena [UNESP]; Leonel, Magali [UNESP]; Leite, Tatiana Dias [UNESP]; Landi Franco, Celia Maria [UNESP]; Mischan, Martha Maria [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2009)
With the advancement of technology, there is the possibility of introduction of differentiated flours, such as cassava instant flour. This alternative has generated great interest from the cassava processing industries. This study aimed to assess the effect of extrusion temperature, moisture content and screw speed on the thermal and viscosity properties of extruded cassava flour. The results showed significant effects of process parameters on the viscosity properties, with effect of screw speed on cold viscosity, viscosity peak and breakdown. The viscosity peak was influenced by the three parameters of extrusion process. No significant effects of operational conditions were observed on the final viscosity and retrogradation. The thermal properties of extruded cassava flours showed no residual enthalpy of gelatinization.
Cassava instant flour: effect of extrusion conditions on thermal and viscosity properties
Keywords: cassava; flour; starch; extrusion; viscosity